Response to pregabalin and progesterone differs in male and female rat models of neuropathic and cancer pain. Issue 1 (1st January 2020) - Ungard, Robert G.; Zhu, Yong Fang; Yang, Sarah; Nakhla, Peter; Parzei, Natalka; Zhu, Kan Lun; Singh, Gurmit
ABSTRACT: Background : Cancer pain involves nervous system damage and pathological neurogenesis. Neuropathic pain arises from damage to the nervous system and is driven by ectopic signaling. Both progesterone and pregabalin are neuroprotective in animal models, and there is evidence that both drugs bind to and inhibit voltage-gated calcium channels. Aims : This study was designed to characterize the effects of progesterone and pregabalin in preclinical models of cancer and neuropathic pain in both sexes. Methods : We measured peripheral sensory signaling by intracellular in vivo electrophysiology and behavioral indicators of pain in rat models of cancer-induced bone pain and neuropathic pain. Results : Female but not male models of cancer pain showed a behavioral response to treatment and pregabalin reduced excitability in C and A high-threshold but not low-threshold sensory neurons of both sexes. Male models of neuropathic pain treated with pregabalin demonstrated higher signaling thresholds only in A high-threshold neurons, and behavioral data indicated a clear recovery to baseline mechanical withdrawal thresholds in all treatment groups. Female rat treatment groups did not show excitability changes in sensory neurons, but all demonstrated higher mechanical withdrawal thresholds than vehicle-treated females, although not to baseline levels. Athymic female rat models of neuropathic pain showed no behavioral or electrophysiological responses to treatment. Conclusions : Both pregabalin and progesterone showed evidence of efficacy in male models of neuropathic pain. These results add to the evidence demonstrating differential effects of treatments for pain in male and female animals and widely differing responses in models of cancer and neuropathic pain.